2008
DOI: 10.1111/j.1439-037x.2008.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitrogen and Gibberellin (GA3) in the Regulation of Enzyme Activities and in Osmoprotectant Accumulation in Brassica juncea L. under Salt Stress

Abstract: Salt stress alters a wide array of plant metabolic mechanisms. Different strategies of the application of nutrients and phytohormones are required to overcome the adverse effects of salt stress. The main objective of the present study was to determine if added nitrogen (N) and gibberellin (GA3) in growth medium could alleviate the adverse effects of salt stress on plant metabolism. Two‐week‐old plants were fed with: (i) 0 mm NaCl + 0 mg N kg−1 sand + 0 m GA3 (control), (ii) 100 mm NaCl + 0 mg N kg−1 sand + 0 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
46
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(56 citation statements)
references
References 67 publications
(70 reference statements)
10
46
0
Order By: Relevance
“…Similar results were reported by Lutts et al (1996), Khan et al (2007) and Siddiqui et al (2008). Salt-stressed plants supplied with CaCl 2 and GA 3 alone or in combination, showed a significant decrease in electrolyte leakage compared to the plants grown with NaCl alone (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were reported by Lutts et al (1996), Khan et al (2007) and Siddiqui et al (2008). Salt-stressed plants supplied with CaCl 2 and GA 3 alone or in combination, showed a significant decrease in electrolyte leakage compared to the plants grown with NaCl alone (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…We infer that Pro and GB accumulation in G 8 might MDA content (nmol g -1 FW) have a role in its salt tolerance. Several reports on different crops are in conformity with these results (Hanson and Burnet 1994;Dubey 1997;Mansour 2000;Ashraf and Harris 2004;Mansour et al 2005;Khan et al 2007;Siddiqui et al 2008). Data revealed that NR activity in Brassica genotypes was inhibited by salt stress (Table 1).…”
Section: Resultssupporting
confidence: 67%
“…Moreover, maximum value for P N , Chl content and g s was observed in genotypes G 8 and G 7 and minimum genotypes G 1 and G 4 under salt stress (Table 2). Malibari et al (1993), Salama et al (1994) and Huang et al (2006) on Chl concentration and Lakshmi et al (1996), Siddiqui et al (2008) on P N and g s , also reported similar results in other plants under salt stress. Therefore, it could be possible reason to suggest that genotype G 8 is less susceptible than other genotypes, because maximum values for these parameters were recorded in genotype G 8 .…”
Section: Resultsmentioning
confidence: 53%
“…Salinity alters many physiological and biochemical processes such as ion toxicity, mineral distribution, respiration rate, organic solutes/osmolytic synthesis, seed germination, enzymes activity and photosynthesis (Marschner 2002;Siddiqui et al 2010). Several studies reported that the high level of NaCl in a growth medium limits the plant growth and development (Gunes et al 2007;Siddiqui et al 2008Siddiqui et al , 2009aSiddiqui et al , 2009bSiddiqui et al , 2010Khan et al 2010). The complexity of salt tolerance mechanisms is varied from plant to plant and cultivar to cultivar and physiological and biochemical processes of plants (Ashraf and McNeilly 2004;Siddiqui et al 2009b).…”
Section: Introductionmentioning
confidence: 94%